Profil Vegetasi Mangrove Desa Sebubus Kecamatan Paloh Kabupaten Sambas - Riza Linda, Purna Habdiansyah, Irwan Lovadi (Universitas Tanjungpura, 2015)
The area of the mangrove forest located in Sebubus Village is not supported by the data and information that provide a description of the forest structure. This research was carried out to find out the vertical and horizontal profile diagram of mangrove vegetation in Sebubus Village, Paloh Sub-district, Sambas Regency, and to find out the influence of the character of environmental factors (salinity, pH, substrate and substrate texture) and mangrove forest zonation patterns. This research was conducted for five months from January to May 2015 in Sebubus Village, Paloh Sub-district, Sambas Regency. The data was collected by making transects at three points. The transects were 30x10 meters in size. Each transect had a sub-plot with the size of 10x10 meters. The observations and measurements were conducted on the identification of tree species, tree height, stem diameter, canopy width, and distance between each tree. The soil samples were taken in each sub-plot to conduct the analysis of the pH value, salinity and substrate structure. The research revealed that the mangrove species found in the site were Brugueira cylindrica (L.) Bl., Brugueira gymnorhiza (L.) Lam., Rhizopora mucronata Lam. and Sonneratia alba Sm.. The zonation patterns formed from the coast to inland were Sonneratia alba Sm., Rhizopora mucronata Lam., Brugueira cylindrica (L.) Bl., and Brugueira gymnorhiza (L.) Lam.. The trees found can be categorized into 3 strata, i.e. 4-9 m, 10-15 m and 16-21 m.